Melacak Jejak Pensyarahan Kitab Hadis - Sandi santosa (Diroyah : Jurnal Studi Ilmu Hadis, 2016)
All Muslims have received understand that the hadith Muhammad Saw is a way of life that is the primary after the Koran . Human behavior is not defined and the laws are still common then no detail later verses of the Koran , then let the solution sought in tradition. And as the Prophet has been around since the beginning of the development of Islam is a fact that can not be doubted. Because the cause and explanation of the hadith is always interesting to be in line with the development of the human mind is increasingly critical . And no wonder then that many parties joined in criticizing the hadith even though they do not understand the science . In this paper the author will explain about Sharh al - hadith, fiqh al - hadith , and the historical development of syarh hadith from time to time.